Waste motor engine oil – the influence in warm mix asphalt - Wan Noor Hin Mior Sani; Ramadhansyah Putra Jaya; Bunyamin Bunyamin; Zaid Hazim Al-Saffar; Yaumal Arbi (Jurnal Pendidikan Teknologi Kejuruan, 2023)
Employing Hot Mix Asphalt (HMA) technology for asphalt pavement construction results in the emission of greenhouse gases and other harmful pollutants, contributing to significant air pollution due to extensive energy consumption. Consequently, the adoption of Warm Mix Asphalt (WMA) is recommended, given its potential for enhanced energy efficiency and reduced emissions due to lower mixing and production temperatures compared to HMA. This research delves into the impact of incorporating waste motor engine oil (WMEO) as a bitumen modifier in warm mix asphalt. The investigation involved adding WMEO at various percentages, specifically 0%, 3%, 4%, and 5% based on the weight of bitumen. The study assessed the performance of the samples in terms of penetration, softening point, stability, flow, and stiffness. The findings revealed that the incorporation of WMEO in warm mix asphalt led to a substantial improvement in penetration and softening point. Moreover, the results indicated that incorporating WMEO as a bitumen modifier could enhance the performance of WMA in terms of stability, flow, and stiffness.